Fabrication of Lamellar Nanosphere Structure for Effective Stress‐Management in Large‐Volume‐Variation Anodes of High‐Energy Lithium‐Ion Batteries. Issue 33 (19th June 2019) - Sung, Jaekyung; Ma, Jiyoung; Choi, Seong‐Hyeon; Hong, Jaehyung; Kim, Namhyung; Chae, Sujong; Son, Yeonguk; Kim, Sung Youb; Cho, Jaephil
Abstract: The use of high‐capacity anode materials to overcome the energy density limits imposed by the utilization of low‐theoretical‐capacity conventional graphite has recently drawn increased attention. Until now, stress management (including strategies relying on size, surface coating, and free volume control) has been achieved by addressing the critical problems originating from significant anode volume expansion upon lithiation. However, commercially viable alternatives to graphite have not yet been found. A new stress‐management strategy relying on the use of a lamellar nanosphere Si anode is proposed. Specifically, nanospheres comprising ≈50 nm Si nanoparticles encapsulated by SiO x /Si/SiO x /C layers with thicknesses of <20 nm per layer are synthesized via one‐pot chemical vapor deposition in various atmospheres. SiO x is found to act as a stress management interlayer when it is located between Si and mitigates stress intensification on the surface layer, allowing nanospheres to maintain their morphological integrity and promoting the formation of a stable solid electrolyte interphase layer during cycling. When tested using an industrial protocol, a full cell comprising a nanosphere/graphite blended anode and a lithium cobalt oxide cathode achieve an average energy density of 2440.2 Wh L −1 (1.72 times higher than that of conventional graphite) with a capacity retention ratio of 80% after 101 cycles. Abstract : A SiO x ‐interlayer within a nanosphere anode, synthesized via a one‐pot chemical vapor deposition (CVD) method, enhances the cyclability of the Li‐ion battery system by sustaining its morphological integrity through mitigating stress intensification. Tested under industrial protocols, this anode exhibits a 1.7 times higher average energy density than conventional graphite. This breakthrough technology sheds light on the practical implementation of large‐volume‐change anodes.